Superiority of SPECT/CT over planar 123I-mIBG images in neuroblastoma patients with impact on Curie and SIOPEN score values - Černý, Igor; Prášek, Jiri; Kašpárková, Helena (Nuklearmedizin, 2016)
OBJECTIVE: The existing most common semi-quantitative systems used for neuroblastoma diagnosis include Curie and SIOPEN scores, which are based on 123I-MIBG planar scans. The purpose of our study was to find out whether a statistically significant difference exists in evaluation based on planar and SPECT/CT scans. We also compared the Curie and SIOPEN methods in terms of their use in regular practice. Patients; method: 45 patients aged 0-10 years; 213 assessments were done in total, and the Curie and SIOPEN scores were determined in each case based on planar and SPECT/CT scans. Student's T-test and the Bland-Altman plot were used for the statistical analysis. RESULTS: Both methods demonstrated a statistically significant difference (p < 0.0001) between planar and SPECT/CT evaluation. In the group of 35 patients with neuroblastoma in clinical stages 3 and 4, in 54% of the patients SPECT/CT detected a lesion that was not visible in the planar scan. In 89% of cases, the lesion was confirmed by another imaging method (CT, MRI). In the group of 10 patients in the clinical stage 1, a difference between planar and SPECT/CT scanning was found only in one patient (10%). In the whole set, 25% patients showed a pathological finding only in soft tissues. CONCLUSION: We recommend to perform semiquantitative evaluation of neuroblastoma based on SPECT/CT scans, particularly in patients in clinical stages 3 and 4. It is advisable to include soft tissues in the score assessment, as well, given that only soft tissues may be involved in up to 25.
Keywords: Female; Infant; dítě; předškolní dítě; novorozenec; ženské pohlaví; 3-Iodobenzylguanidine; 3-jodobenzylguanidin; Reproducibility of Results; radiofarmaka; lidé; Infant, Newborn; staging nádorů; Sensitivity and Specificity; vylepšení obrazu; Single Photon Emission Computed Tomography Computed Tomography; senzitivita a specificita; Image Enhancement; reprodukovatelnost výsledků; Male; kojenec; Child, Preschool; Neuroblastoma; Radiopharmaceuticals; SPECT/CT; pozitronová emisní tomografie; Child; neuroblastom; mužské pohlaví; Neoplasm Staging; Positron-Emission Tomography; Humans